Mewujudkan masa depan bersih: Menggali konsep dan manfaat ekonomi hijau - TAUFIK, A. MUQIT (Maliki Interdisciplinary Journal, 2025)
A green economy is a development approach that prioritizes economic growth in harmony with environmental conservation and social justice. This concept emerged in response to the increasing impacts of climate change, environmental degradation, and the need for sustainable development. Through the principles of low-carbon development, resource efficiency, and inclusivity, a green economy offers a more environmentally friendly development model that can provide balanced economic and social benefits. This article discusses the definition, basic concepts, and examples of the application of a green economy as an effort to realize a cleaner, healthier, and more sustainable future.